Patterns and Severity of Alcohol Consumption in Patients with Alcoholic Liver Disease: A Cross-Sectional Study - Niroula, Niju (Journal of Nepalgunj Medical College, 2021)
Introduction: Alcohol is a known cause of liver cirrhosis, with its incidence increasing in relation to the total amount and duration of intake. Excessive consumption of alcohol remains the main cause of alcohol-related liver disease and associated complications and deaths.Aims: To delineate the drinking patterns and severity of alcohol consumption in alcoholic liver disease patients.Methods: A descriptive cross sectional study was conducted among 95 patients of both sexes with the diagnosis of alcoholic liver disease (ALD), who were admitted in Medicine ward at Nepalgunj Medical College, Nepalgunj. The diagnosis of ALD was confirmed by the criteria of the ICD-10-CM. The severity of alcohol drinking screened and categorized as “low-risk drinkers,” “hazardous drinkers,” and “harmful drinkers” were based on the AUDIT score.Results: Among a total of 95 ALD patients, the mean age was 45.10 ±7.60 years, the mean duration of alcohol use was 22.6 ±7.65 years and the average amount of alcohol consumed in grams/day was 240 ± 35. Majority of the patients consumed locally brewed alcohol, Raksi 46.3% followed by Jaad 22.1% and Others 11.6%. Very few patients consumed commercially available Spirits 6.3% or Beer 13.7%. Majority of patients were found to be drinking regular with intermittent bingeing pattern 61%, outside meal times 69.5% and hazardous drinking 53.7%.Conclusion: Overall our analyses indicated a precise picture of drinking patterns in ALD patients that are profoundly influenced on several cofactors like alcohol type, duration of exposure, drinking patterns, cultural habits, availability of homemade beverages and individual susceptibility. We recommend screening for alcohol abuse in all adult patients presenting to the hospital as early detection of ALD can decrease its both morbidity and mortality.